Al Kalimaat Al Murokkabah Min Mu’jam Al-Lughoh Al Indunisiyyah Wa Ta Tsiruha Ala Lughah Muta’alimi Al Lughah Al-’Arobiyah Al-Mubtadiin Al-Indunisiyyin - Herni Khoirunnisa; Syirojul Huda (Mauriduna: Journal of Islamic Studies, 2021)
تهدف هذه الدراسة إلى تحليل الكلمات المركبة من القواميس الإندونيسية الكبيرة وإيجاد تأثيرها على متعلمي اللغة العربية. يعتمد هذا البحث على الأساليب العلمية ، وهي: الطرق: الأوصاف التحليلية للنهج الكمية والنوعية. طريقة تحليل البيانات النوعية المستخدمة هي الطريقة المستخدمة للإشارة إلى المكون المباشر. طريقة التحليل الكمي للبيانات هي ضرب عدد التكرارات في المئة وتقسيمها على عدد العينات. نتائج البحث 1). تحتوي الكلمات الإندونيسية المركبة التي تتوافق مع الصيغة العربية على 19 كلمة. 2). الكلمات الإندونيسية المركبة التي تنتهك بنية اللغة العربية وتحتوي على 28 كلمة. تدخل الكلمات الإندونيسية المركبة مصطلحات نحوية اصطلاحية باللغة العربية وتحتوي على 9 كلمات. أظهرت النتائج أن 72٪ من الطالبات يجدون صعوبة في استخدام الكلمات المركبة الإندونيسية المكافئة باللغة العربية ، و 38٪ من الطالبات يترجمون الكلمات الإندونيسية المركبة حرفياً ، و 28٪ أن الطالبات لا يعرفن الكلمات الإندونيسية المركبة المكافئة في اللغة العربية من قبل ، و 88 ٪ من الطالبات يعرفون ويدركون أن الكلمات الإندونيسية المركبة باللغة العربية مهمة جدًا لمعرفة خاصة للطلاب العرب ، و 96 ٪ من الطلاب ، والكثير منهم مخطئون في استخدام الكلمات الإندونيسية المركبة باللغة العربية. This study aims to analyze compound words from large Indonesian dictionaries and find their effect on Arabic language learners. This research is based on scientific methods, namely: Methods: Analytical descriptions of qualitative and quantitative approaches. The qualitative data analysis method used is the approach used to refer to the direct component. Quantitative data analysis method is to multiply the number of repetitions by percent and divide it by the number of samples. Results from research 1). Indonesian compound words, which match the Arabic syntax, contain 19 words. 2). Indonesian compound words that violate the structure of the Arabic language and contain 28 words. Indones ian compound words enter idiomatic syntactical terms in Arabic and contain 9 words. The results showed that 72% of female students found it difficult to use equivalent Indonesian compound words in Arabic, 38% of female students translated Indonesian compound words literally, and 28% that female students did not know equivalent Indonesian compound words in Arabic before, and 88% of female students know and realize that Indonesian compound words in Arabic are very important to know especially for Arabic students, and 96% of students, many of them wrong in using Indonesian compound words in Arabic.